A BRIEF HISTORY OF THE SONATA FORM (I) THE BAROQUE SONATA - Emanuela-Fabiola PRIP (Studia Universitatis Babeş-Bolyai. Musica, 2020)
In this short study, we aim to define the typologies of the sonata form in the music of the Baroque period, alongside the perspective of some well-known authors (Charles Rosen, James Webster or William Newman) and to propose two analyses – the Sonata in G minor, K. 450 composed by D. Scarlatti and part I from the Sonata in A major, Wq. 55/4 by C. Ph. E. Bach. An interesting point of this study is the connection and the transition from the monothematic sonata form to the bithematic sonata form.